2019
DOI: 10.3389/fncel.2019.00566
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of AM404 Against NMDA-Induced Hippocampal Excitotoxicity

Abstract: Different studies have demonstrated that inflammation and alterations in glutamate neurotransmission are two events contributing to the pathophysiology of neurodegenerative or neurological disorders. There are evidences that N-arachidonoylphenolamine (AM404), a cannabinoid system modulator and paracetamol metabolite, modulates inflammation and exerts neuroprotective effects on Huntington's (HD) and Parkinson's diseases (PD), and ischemia. However, the effects of AM404 on the production of inflammatory mediator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 62 publications
(64 reference statements)
0
11
0
Order By: Relevance
“…In murine 4-aminopyridine-induced epileptic hippocampal neurons, AM404 reduced anandamide- and capsaicin-induced Ca 2+ -accumulation, apoptosis and ROS-generation ( Nazıroğlu et al, 2019 ). In our previous studies, we showed the reduction of LPS-induced PGE 2 and 8-isoprostane release by AM404 in concentration-dependent manner in primary rat microglia ( Saliba et al, 2017 ) and N-methyl-D-aspartate (NMDA)-induced IL-1β-expression in organotypic hippocampal slice cultures (OHSC) of mouse brain ( Saliba et al, 2019 ). Furthermore, COX-2 protein levels and COX-activity induced by LPS were significantly reduced by AM404.…”
Section: Introductionmentioning
confidence: 99%
“…In murine 4-aminopyridine-induced epileptic hippocampal neurons, AM404 reduced anandamide- and capsaicin-induced Ca 2+ -accumulation, apoptosis and ROS-generation ( Nazıroğlu et al, 2019 ). In our previous studies, we showed the reduction of LPS-induced PGE 2 and 8-isoprostane release by AM404 in concentration-dependent manner in primary rat microglia ( Saliba et al, 2017 ) and N-methyl-D-aspartate (NMDA)-induced IL-1β-expression in organotypic hippocampal slice cultures (OHSC) of mouse brain ( Saliba et al, 2019 ). Furthermore, COX-2 protein levels and COX-activity induced by LPS were significantly reduced by AM404.…”
Section: Introductionmentioning
confidence: 99%
“…The way in which NO and eicosanoid biosynthesis pathways are linked is not yet known 165‐167 . Moreover, recent studies have shown that AM404 exhibits a neuroprotective effect against NMDA‐induced hippocampal excitotoxicity, and could find application as a neuroprotective agent in Huntington's and Parkinson's diseases and ischaemia 67,168 …”
Section: Paracetamol – Other Mechanisms Of Actionmentioning
confidence: 99%
“…VB-037 is a quinoline compound protecting neurons against Aβ aggregates-induced cytotoxicity through reduction of P38- and JNK-mediated inflammation [ 30 ]. In addition, anandamide transport inhibitor AM404 (C 26 H 37 NO 2 ) displays anti-inflammatory and neuroprotection effects on N-methyl-D-aspartic acid (NMDA)-induced excitotoxicity [ 31 ]. In the present study, we examined the anti-inflammatory effects of AM404, VB-037, glycyrrhizic acid, SG-Tang, and G. inflata on BV-2 microglia and inducible A53T SNCA-GFP-expressing SH-SY5Y cells.…”
Section: Introductionmentioning
confidence: 99%